Association Between Air Flow Limitation and Body Composition in Young Adults - Garcia-Herrera, C (BioMed Central Ltd, 2021)
Background: Body composition (BC) influences respiratory system mechanics, provoking air flow limitation (AFL). The objective of this study was to determine the relationship of AFL in small- and medium-caliber airways with BC in young adults. Methods: Eighty-three individuals were recruited (40 men and 43 women). To determine AFL, the following measurements were taken: forced expiratory volume in the first second (FEV1), forced expiratory flow between 25 and 75% (FEF25–75%), airway resistance (Raw), and specific airway resistance (sRaw). The measured BC variables were body mass index (BMI), body fat percentage (%BF), and fat-free mass (FFM). Binary logistical regression analysis was used to estimate the association between the AFL variables and %BF, BMI, and %FFM, adjusting for weight and gender. Results: Among men, a relationship was observed between Raw and %BF (r = 0.728; p < 0.0001) and sRaw and BMI (r = 0.617; p < 0.0001). Among women, significant relationships were reported between Raw and BMI (r = 0.615; p < 0.0001) and sRaw and BMI (r = 0.556; p < 0.0001). Among participants with a BMI over 30 kg/m2, higher risks of increased Raw (OR = 26.8; p = 0.009) and sRaw (OR = 9.3; p = 0.002) were observed. Furthermore, higher %BF was associated with greater risks for increased Raw (OR = 14.04; p = 0.030) and sRaw (OR = 4.14; p = 0.028). In contrast, increased %FFM (OR = 0.14; p = 0.025) was a protective factor for lung function. Conclusion: Increased %BF is associated with increased AFL in small-caliber airways. Furthermore, increased %FFM is associated with decreased risk for Raw and sRaw in women. Therefore, evidence indicates that increased %FFM is a protective factor for adequate lung function. © 2021, The Author(s).